Carboplatin and Liposomal Doxorubicin for Ovarian Cancer. Issue 6 (June 2016) - Nguyen, Jamie; Solimando, Dominic A.; Waddell, J. Aubrey
The complexity of cancer chemotherapy requires pharmacists be familiar with the complicated regimens and highly toxic agents used. This column reviews various issues related to preparation, dispensing, and administration of antineoplastic therapy, and the agents, both commercially available and investigational, used to treat malignant diseases.